Challenges and understandings of creative practice in professional sport training - Philippe, A. G.; Biasutti, M.; van der Schyff, D.; Schiavio, A. (PLOS ONE, 2023)
We conducted a qualitative study involving twelve expert sports coaches to explore and compare the range of creative practices they adopted during their professional activities. Their written responses to open-ended questions highlighted different interrelated dimensions of creative engagement in coaching sport, suggesting that efforts to instil creativity may initially focus on an individual athlete; they may often span a range of behaviours dedicated to efficiency; they may involve significant degrees of freedom and trust; and they cannot be captured by a single defining feature. We contextualise these findings in the light of recent literature in sports studies, performance science and creativity research, providing concrete examples based on the written statements provided by our participants. We conclude by offering insights for future research and coaching practice that may be relevant in broader domains.